Inclusivity in Preserving the Mappogau Sihanua Tradition in the Karampuang Indigenous People from a Cultural Determinism Perspective - Andi Nurannisa; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Muhammad Safar; Andi Nurhidayah Abidin; Ayu Handira (Yayasan Keluarga Guru Mandiri, 2024)
The Karampuang Indigenous People are still actively carrying out rituals to worship the spirits of their ancestors as a form of thanksgiving and a wish for a better life. However, for some of the Karampuang Indigenous people, this ritual is only a form of gratitude and respect for traditional leaders. This research aims to explore and reveal how the Mappogau Sihanua ritual influences and shapes religious, social, and cultural values in Karampuang Indigenous peoples. This research was conducted using a qualitative descriptive method with the subject, namely the people in the location of the Karampuang Traditional Village, Tompobulu Village, Bulupoddo District, Sinjai Regency. Through the stages of analysis, including data reduction, data presentation, and data verification in the form of observation, interviews, and documentation, the findings reveal several efforts that can be made to preserve Karampuang Indigenous culture. This study shows that the ritual tradition of Mappogau Sihanua needs to be preserved by increasing inclusivity so that it can be accepted by the wider community, including people who do not understand myths that are considered sacred. The acknowledgment of various cultural identities in society is made possible by inclusivity. Within the Karampuang traditional community, maintaining the Mappogau Sihanua custom can symbolize acknowledging the plurality of cultures.